Ecological systems theory as a framework for understanding the individual plan of study: a qualitative case study of three Kansas high schools - Smith, Stacy (Kansas State University, 2021)
This qualitative case study examined the individual plan of study (IPS) within three comprehensive high schools. Ecological systems theory was used as a construct for understanding the actions of the participants and their interactions within the ecology in support of the success of each student. Participants in this research shared their understandings of the individual plan of study priorities as well as their experiences in the organization and delivery of services in the support of each student. Kansas communities face increasingly complex circumstances including generational, cultural, and economic change. Kansas high schools contribute to the development of students and their capacity to navigate these changes and launch into a successful young adulthood. Supporting students in early complex decision making regarding their educational journey has the potential to profoundly impact their lifespan outcomes. The research question explored the role that school counselors play in supporting student experiences through an organization of ecological members. The research further explored the relationships within the ecological system that students experienced and the roles or activities that members of the ecology filled to support the completion of individual plan of study activities which informed the growth of the student. The literature study established the foundational nature of the individual plan of study as representative of experience-making that occurred as students grew and developed forming their understandings of themselves, their education, and their continuing journey. The literature examined the roles of school counselors in the comprehensive high school, examined career development models, and explored the importance of such learning experiences as applied learning, contextual learning, and career and technical education in supporting student achievement. As a bounded case study, data was collected from personal interviews, a focus group discussion, and examination of artifacts submitted by interview participants. Completed during the Covid 19 event, the delivery of individual plan of study services were unique to the year. Outside of major urban areas these three comprehensive high schools were primarily in-person learning environments throughout most of the year with periodic tilts toward hybrid instruction, and instances of individual quarantine affecting students, staff, community, and family in unique and individual ways. This study’s key findings contribute to the study of ecological systems theory as well as career development. Evidence showed that counselors representing the whole staff within the ecological system were facilitating the individual plan of study in ways that supported the connection of ecological members to provide support for student learning. The school counselors gained confidence and satisfaction through their actions which also supported the function of engaging other members of the ecology. Data suggested that school counselors’ success was supported through strong organizational elements that provided a vehicle for arranging and engaging intersections which benefit student growth and experience. The data illustrated the importance of activities which included families, school staff, and communities as significantly important to providing a wide range of opportunities and experience, which when available fostered student capabilities. Where these parties were able to converge, students experienced increased opportunities for engagement. There is potential for this study to have broad implications in schools as each student from the middle grades through twelfth grade is mandated by the Kansas State Board of Education to create and maintain an individual plan of study. Each year school counselors are supported in the foundational ideas of the individual plan of study. An understanding of ecological systems theory will conceptualize knowledge, structures, and activities supporting the implementation of the individual plan of study and improve school counselors’ perspective toward services. This may prove to be a transformative experience for a community as their students experience and grow through these implemented activities.
Keywords: School counselors; Individual plan of study; Ecological system